Wykorzystanie metod logistycznych w rolnictwie jako stymulatora poprawy konkurencyjności na przykładzie planowania potrzeb dystrybucyjnych w ujęciu przepływu pasz do hodowców drobiu - Szpon, Jakub (Logistic Methods Use in Agriculture as Stimulator of Competitiveness Improvement on the Example of Distribution Needs Planning from the Perspective of Fodder Flow to Poultry Farmers, 2005)
In logistic spheres according to division stage near distribution and production sphere it is possible to separate distribution connected with final products allocation on outside markets. For better production competitiveness fanners should use logistic tools which optimize flow e.g. fodder (which is an essential poultry breeding cost component). Therefore, it is crucial to create mechanisms which enable reduction fodder price through rational management in an established supply chain (fodder producer-breeder), e.g. distribution needs planning method is applied.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 332-337